American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
American Civil Liberties Union staff attorney Alan Schlosser introducing Howard Watkins Luncheon at Sheraton Palace Hotel in San Francisco